The physiology and pathology of coagulation factor XI - Gailani, David (Henry Stewart Talks, 2007)
Discovery of coagulation factor XI, Structure of factor XI, Normal plasma coagulation, Mechanisms for factor XI activation, Inherited factor XI deficiency, Factor XI in mouse thrombosis models
Archived at 2016/07/07